LBM-HPC - An Open-Source Tool for Fluid Simulations. Case Study: Unified Parallel C (UPC-PGAS) - Valero-Lara, Pedro; Jansson, Johan (Proceedings / IEEE International Conference on Cluster Computing, 2015)
The main motivation of this work is the evaluation of the Unified Parallel C (UPC) model, for Boltzmann-fluid simulations. UPC is one of the current models in the so-called Partitioned Global Address Space paradigm. This paradigm attempts to increase the simplicity of codes and achieve a better efficiency and scalability. Two different UPC-based implementations, explicit and implicit, are presented and evaluated. We compare the fundamental features of our UPC implementations with other parallel programming model, MPI-OpenMP. In particular each of the major steps of any LBM code, i.e., Boundary Conditions, Communication, and LBM solver, are analyzed.